Reevaluation of Geothermal Potential of Çubukludağ Graben (Western Anatolia, Turkey) - Ozdemir, Adil; Arabaci, Fahri; Palabiyik, Yildiray (Ekrem KALKAN, 2020)
This study aims to determine the geometrical, structural features, and geothermal potential of the Çubukludağ Graben. Within the study’s scope, fault-fracture and layer planes were measured at 110 stop points and plotted to the rose diagram and Wulff net. Thus, geological sequence, fault orientations, types and geometries, intersection areas, and lateral and vertical displacements of the faults, tensional-compressional areas, main compression directions, and rotation regions were determined. The geological and morphotectonic maps of the region were prepared. The formation mechanisms of the hanging rhyolite and dacite caps, along with the large-sized tears in the middle and west of the graben, were also explained using those maps. The main tectonic structures and the faulting characteristics of the Tuzla, Deliömer, Gümüldür and Değirmendere Fault Zones that boundary these structures, and the relations between the geological setting and the geothermal system are detailed. In the light of the new field data obtained, a new geological model of the graben has been constructed, and the geothermal potential has been reevaluated.
Keywords: Çubukludağ Graben; Western Anatolia; Tuzla Fault Zone; High-temperature geothermal field; Geothermal potential; Geological Sciences and Engineering (Other); Yer Bilimleri ve Jeoloji Mühendisliği (Diğer)